Selective Inhibition of Newcastle Disease Virus-Induced Glycoprotein Synthesis by d-Glucosamine Hydrochloride - Samson, A. C. R. (1974)
d-Glucosamine selectively affected the synthesis of virus-induced glycoproteins in Newcastle disease virus-infected chick fibroblasts, but had no effect upon post-translational cleavage of the glycoprotein precursor for one of the two major glycoproteins of the mature virion. In response to glucosamine, at least one of the two virus-induced glycoproteins is formed in reduced quantity and the second is either not formed or has an electrophoretic mobility identical to that of another virus-induced protein.